The Ocean and Cryosphere in a Changing Climate in Latin America: Knowledge Gaps and the Urgency to Translate Science Into Action - Muelbert, Mônica M. C.; Copertino, Margareth; Cotrim da Cunha, Leticia; Lewis, Mirtha Noemi; Polejack, Andrei; Peña-Puch, Angelina del Carmen; Rivera-Arriaga, Evelia (Frontiers in Climate, 2021)
Climate Change hazards to social-ecological systems are well-documented and the time to act is now. The IPCC-SROCC used the best available scientific knowledge to identify paths for effective adaptation and mitigation of climate change impacts on the ocean and cryosphere. Despite all the evidence highlighted by SROCC and the key role of the ocean and cryosphere for climate change at all levels, Latin America (LA) faces challenges to take effective action mostly due to socio-economic vulnerability, political instability and overall technical capacities. Countries have adopted diverse actions as the information needed by policy makers has been made available, not necessarily in accessible and inclusive ways. Regional imbalance in economic development, technological level, capacity development, societal involvement, and governmental oversight have contributed to skewed geographical and technological gaps of knowledge on key ecosystems and specific areas preventing effective climate actions/solutions. We analyze the Nationally Determined Contributions (NDCs) from the region as proxies to the incorporation of IPCC recommendations. The gaps and opportunities for the uptake of ocean and climate science to political decision making is discussed as five key aspects: (i) climate assessment information and regional policies, (ii) knowledge production, (iii) knowledge accessibility, (iv) knowledge impact to policy, and (v) long term monitoring for decision making. We advocate that the uptake of SROCC findings in LA policies can be enhanced by: (a) embracing local realities and incorporating local, traditional and indigenous knowledge; (b) empowering locals to convey local knowledge to global assessments and adapt findings to local realities; (c) enhancing regional research capabilities; and (d) securing long-term sustainable ocean observations. Local and regional participation in knowledge production and provision enhances communication pathways, climate literacy and engagement which are key for effective action to be reflected in governance. Currently, the lack of accessible and inclusive information at the local level hampers the overall understanding, integration and engagement of the society to mitigate climate effects, perpetuates regional heterogeneity and threatens the efforts to reverse the course of climate change in LA. Local researchers should be empowered, encouraged, rewarded and better included in global climate-ocean scientific assessments.